Learning Journal Strategy to enhance students’ writing ability - Shaumiwaty Shaumiwaty (Universitas Merdeka Malang, 2020)
This research aims to find out the students writing ability by using learning journal strategy. In to do that, the experiment methods with one group pretest and posttest design was used. The population in this research was 218 students at eight grade (VIII) of Secondary students on MTsN Takengon I. As the research sample, it was chosen two classes, i.e. VIII1 as the experiment class and VIII2 as the control class. The pre-test was given and it was followed by the treatments in four meetings to the students. The data were analyzed using t-test to reveal whether there was a significant difference in the students’ writing ability of descriptive text among the eight grade students of MTsN Takengon I. The results of this study indicate that the t-test was 2.10 and t-table was 1.07. Therefore Ho is rejected and Ha is accepted because the t-test is higher than the t-table. DOI: 10.26905/enjourme.v4i2.4238